Оцінка впливу гідравлічного опору ФТЧ на паливну економічність дизеля - Кондратенко, Олександр Миколайович; Строков, Олександр Петрович; Вамболь, Сергій Олександрович (НТУ "ХПІ", 2014)
Проведено стендові випробування автотракторного дизеля 2Ч10,5/12, випускна система якого оснащена фільтром твердих частинок, розробленим у відділі поршневих енергоустановок Інституту проблем машинобудування ім. А. М. Підгорного НАН України. Отримано витратні характеристики ФТЧ дизеля шляхом прямих вимірювань. При аналізі результатів випробувань до них застосовано стандартизований підхід, що міститься у нормах токсичності ВГ автотранспортних засобів Європейської Спілки, які чинні і на території України та Російської Федерації. Також застосовано розроблену методику оцінки впливу гідравлічного опору ФТЧ на паливну економічність дизеля на базі положень Теорії ДВЗ.

Bench tests of the vehicle diesel engine 2Ch10.5/12 with particulate matter filter (DPF) in its exhaust system was provide. The DPF was designed in the Piston plants dept. of the A. N. Podgorny Institute for Mechanical Engineering Problems of the National Academy of Sciences of Ukraine (IPMash of NAS of Ukraine). Achieved the flow characteristics of the DPF by direct measurements. When the results of tests was analyzing applied the standardized approaches which contained in exhaust emissions standards for vehicles of the European Union which are valid in Ukraine and Russian Federation. Also used the developed method of assess of influence of hydraulic resistance of DPF on fuel efficiency of diesel engine which based on provisions of the Theory of internal combustion engines. Data for evaluation of the working parameters of the diesel engine, parameters of the toxicity of its exhaust gases and of efficiency indicators of the DPF are obtained by linear regression describing of the data that characterize the work of diesel on the following characteristics: the outside speed, load with rotational speed of the diesel crankshaft of mode with the maximum torque, load with rotational speed of the diesel crankshaft of mode with maximum power, the characteristic of idling.
Estimation of influence of hydraulic resistance of DPF on the fuel efficiency of diesel engine
Keywords: екологічна безпека; фільтр твердих частинок; двигуни внутрішнього згоряння; норми токсичності; гідравлічний опір; паливна економічність; environmental safety; particulate matter filter; internal combustion engines; emission standards; hydraulic resistance; fuel efficiency